Ekonomiczne uwarunkowania korupcji - Brol Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The corruption exists in almost every kind of relationship between at least two subjects. The aim of this paper is to point the economic causes of the corruption. It is also a review of some of the economic theories that deal with this problem. The bribe can be discussed at four grounds: as a payment that equates supply and demand, as incentive payments to bureaucrats, as a cost reduction and as a possibility for crime. On these grounds the author shows the costs and the benefits of bribery. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 48-55